Enhancing second harmonic generation-mediated photodynamic therapy via external electric field modulation - Manu Kumar; Avinash Jukanti; Rivka Cahan; Dima Cheskis; Refael Minnes (PLoS ONE, 2026)
Photodynamic therapy (PDT) utilizes light-activated photosensitizers (PS) to produce reactive oxygen species (ROS) for targeted bacterial destruction; however, its efficacy is often limited by inadequate light penetration, necessitating novel enhancements, such as the integration of second harmonic generation (SHG) through harmonic nanoparticles (HNPs) that convert two photons into one of higher frequency, thereby advancing the approach of SHG-based PDT for improved bacterial eradication. Our novel technique explores the impact of an e (EEF) on SHG intensity to augment PDT efficacy against Staphylococcus aureus ( S. aureus ). We investigated a novel conjugate, Bismuth Ferrite (BFO) in conjunction with protoporphyrin IX (PPIX), and compared it to the Barium Titanate (BT)-PPIX conjugate, under EEF of 0 V, 10 V, and 20 V for a duration of 5 minutes. The experiments utilized a near-infrared (NIR) femtosecond pulsed laser at 798 nm for excitation. Our findings show that EEF significantly enhances SHG intensity, improving photodynamic activity. Notably, BFO-PPIX conjugates significantly decreased bacterial survival to 35.8 ± 3.0% under EEF exposure, in contrast to 48.1 ± 3.2% without EEF. Similarly, to further substantiate the impact of EEF on SHG-based PDT efficacy, BT-PPIX conjugates resulted in bacterial survival of 57.1 ± 1.0% with EEF exposure, in contrast to 78.4 ± 3.7% without EEF. Our findings confirm the first study of EEF-modulated SHG in PDT, demonstrating its capacity to augment SHG intensity in HNPs-PPIX conjugates and improve therapeutic efficacy. These results highlight the potential of SHG-enhanced PDT, particularly with optimized EEF.